Suspected chlorfenapyr poisoning in a horse - Simões, B. P. [UNESP]; Cerri, F. M. [UNESP]; Takahira, R. K. [UNESP]; Borges, A. S. [UNESP]; Oliveira-Filho, J. P. [UNESP]; Amorim, R. M. [UNESP] (Elsevier, 2025)
Chlorfenapyr is a pesticide that interferes with mitochondrial function, leading to cell death and mortality. Although poisoning is primarily documented in humans and dogs, it can result in severe clinical signs, including sweating, respiratory distress, and neurological dysfunction. This report describes the clinical and laboratory findings of a horse with suspected accidental intoxication with chlorfenapyr. A 4-year-old Quarter Horse mare was referred to the veterinary hospital with signs of excessive sweating, hyperthermia, tachypnea, muscle fasciculation, and fearful facial expression. The clinical signs appeared a day after the paddock where the horse grazed was sprayed with chlorfenapyr for caterpillar control. Despite initial abnormalities in renal and liver profiles in the serum biochemistry analysis, the horse responded positively to supportive treatment with intravenous fluid therapy, sodium dipyrone (25mg/kg QID), and cold-water showers, showing improvement in clinical parameters, and was discharged without further complications.
Keywords: Equine; Hyperthermia; Hypochloremia; Sweating; Toxicity